How Micro-Geometry of Cutting Edges Influences Surface Integrity - Nilsson, Isak; Steen, Karl (My University, 2026)
The aerospace industry relies heavily on the structural integrity of machined components. Even the smallest surface and subsurface defects can drastically reduce the components’ fatigue life, possibly resulting in catastrophic failure. This thesis quantitatively evaluates the impact of cutting edge micro-geometry. Specifically, how edge radius and symmetry affect surface integrity during the machining of Ti- 6Al-4V. A fundamental experimental study has been conducted to investigate how changes in a cutting edge’s sharpness and shape, its micro-geometry, affect the surface integrity of the machined part. A series of orthogonal cutting tests in Ti-6Al-4V was made to investigate the elementary relationship between cutting edge microgeometry and surface integrity under different cutting conditions. The results are evaluated through regression analysis to statistically describe the relationships. It was found that cutting tools with larger radii and waterfall-shaped edges strongly impact surface integrity, regardless of variations in cutting speed and depth of cut. Other surface integrity variables, however, do depend on cutting speed and depth of cut, not just on cutting edge micro-geometry.
Keywords: Aerospace; Machining; Surface Integrity; Experimental Study; Cutting edge micro-geometry; Characterization; Regression model